Penerapan Audit Manajemen Untuk Menilai Ekonomisasi, Efisiensi Dan Efektivitas Fungsi Pengadaan Barang Dan Jasa: Studi Kasus pada PT. PLN ULP Ruteng, Nusa Tenggara Timur - Beata Sakristi Sarni; Tries Ellia Sandari (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This study discusses the management audit on the function of procurement of goods and services. Management audit is a tool for management audit is a tool that can be used by companies to measure the economy, effectiveness, and efficiency or evaluation of management activity programs. This study aims to assess the economization, efficiency, and effectiveness of the function of the procurement of goods and services at PT PLN ULP Ruteng. The scope of the procurement function includes the procurement organization, the procurement process which consists of: procurement planning, procurement implementation, payment and reporting. In this study, it is more specifically discussed about the audit of goods and services procurement organizations. Presidential Regulation No. 16 of 2018 states that the Government Goods/Services Procurement Policy Agency, hereinafter referred to as LKPP, is an institution tasked with developing and formulating policies for the Government's procurement of goods/services. This research is a qualitative research with a case study approach. Data collection techniques used are observation, interviews, and documentation. The method of data analysis is carried out with the elements of the management audit, the data obtained will be classified into the Criteria, Conditions, Causes, Effects groups. From the results of research on the procurement function in the organization of procurement of goods and services PT PLN ULP Ruteng it cannot be said to be effective and efficient. From the specified criteria, there are weaknesses in this program. The recommendations given by researchers to companies can be used as material to make improvements to these weaknesses.